2006
DOI: 10.1007/s00125-006-0339-8
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal viral exposure followed by adult stress produces glucose intolerance in a mouse model

Abstract: Aims/hypothesis It has been suggested that the uterine environment may influence metabolic disease occurring later in adult life, and that adult stress may promote disease outcome. Using a mouse model, we tested whether in utero exposure to Ljungan virus (LV) followed by adult exposure to stress produces diabetes. The influence of the timing of viral exposure over the course of pregnancy was also tested. Materials and methods Pregnant CD-1 mice were exposed i.p. to LV on pregnancy days 4, 8, 12 or 17. Adult ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…Similar results were obtained in a mouse model, in which pregnant mice were infected with Ljungan virus (LV), a virus that belongs to the Picornavirus family and is virulent for laboratory rodents (126). Maternal LV exposure in mice has been shown to predispose the offspring to signs of Type 2 diabetes and obesity (110). These effects, however, were particularly manifest in LV-exposed mice that experienced additional stress during adolescence, suggesting that the severity of metabolic abnormalities following prenatal immune activation can be exacerbated by exposure to other environmental adversities, such as adolescent stress (110).…”
Section: Obesity and Metabolic Dysfunctionssupporting
confidence: 58%
See 1 more Smart Citation
“…Similar results were obtained in a mouse model, in which pregnant mice were infected with Ljungan virus (LV), a virus that belongs to the Picornavirus family and is virulent for laboratory rodents (126). Maternal LV exposure in mice has been shown to predispose the offspring to signs of Type 2 diabetes and obesity (110). These effects, however, were particularly manifest in LV-exposed mice that experienced additional stress during adolescence, suggesting that the severity of metabolic abnormalities following prenatal immune activation can be exacerbated by exposure to other environmental adversities, such as adolescent stress (110).…”
Section: Obesity and Metabolic Dysfunctionssupporting
confidence: 58%
“…Maternal LV exposure in mice has been shown to predispose the offspring to signs of Type 2 diabetes and obesity (110). These effects, however, were particularly manifest in LV-exposed mice that experienced additional stress during adolescence, suggesting that the severity of metabolic abnormalities following prenatal immune activation can be exacerbated by exposure to other environmental adversities, such as adolescent stress (110). These findings are particularly relevant for the multifactorial etiology of obesity and Type 2 diabetes, which are likely caused by a combination of environmental (and genetic) factors (38,81).…”
Section: Obesity and Metabolic Dysfunctionsmentioning
confidence: 99%
“…However, its possible role in the development of diabetes in the bank voles remains to be proven. It has been shown in CD-1 mice that when the mother is inoculated with the Ljungan virus during gestation the offspring develops diabetes (Niklasson et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Its possible role in the development of diabetes in the bank voles remain to be proven. It has been shown that the CD1 mouse offspring develop diabetes when the mother is inoculated with the Ljungan virus during gestation (Niklasson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%